Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) Associated With Iodinated Contrast Media: A Case Report with Fatal Outcome and Literature Review - Navarro, Andrea; Rios Bracamontes, Eder Fernando; Teresa de Jesús Ortiz Tejeda; Ocampo Carrasco, Ivanna (International Journal of Medical Science and Clinical Research Studies, 2025)
An adverse drug reaction (ADR) is defined by the World Health Organization (WHO) as any harmful and undesired response to a drug that occurs at doses normally used in humans for prophylaxis, diagnosis, treatment of a disease, or to modify a physiological function (1). Cutaneous adverse drug reactions (CADRs), or pharmacodermias, are a type of ADR that manifest in the skin, mucous membranes, and/or appendages (1). Their broad clinical presentation can pose a diagnostic challenge. Currently, with the constant development of new diagnostic and therapeutic options, exposure to various types of medications has increased, necessitating a high index of suspicion and the ability to detect any manifestation of a potential ADR. Furthermore, there is limited information on ADRs related to iodinated contrast media, as non-immediate hypersensitivity reactions are estimated to occur in only 0.5% to 3% of exposed patients, with even fewer reported cases of severe, potentially life-threatening reactions. We present the case of a patient with chronic exposure to medications for managing comorbidities, who developed a drug reaction with eosinophilia and systemic symptoms (DRESS) following exposure to iodinated contrast media as part of his diagnostic and therapeutic workup, ultimately leading to his death.